O valor informativo das histórias em quadrinhos como canal de divulgação científica - (:unkn) unknown (Universidade Federal do Rio de Janeiro / Instituto Brasileiro de Informação em Ciência e Tecnologia, 2012)
Research on comic strips - comics as a tool for scientific dissemination, under the approach of Information Science and having, as theoretical basis, the concepts of information, the relationship between science and scientific dissemination, and the analysis of the latter s origin, categories, current functions, language and educational role. Some examples of comics, like The Manga Guide, Donald in Mathmagic Land and Goofy as a Famous Historical Person, demonstrate the value of image as illustration and information and the potential of comic books as an instance of language that can be turned into a tool of scientific dissemination
The informative value of comics as a channel of scientific communication
Keywords: Comic books; Information; Scientific dissemination; História em quadrinhos; Informação; Divulgação científica; CNPQ::CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO